2013
DOI: 10.1002/bjs.9114
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sacral nerve stimulation on distal colonic motility in patients with faecal incontinence

Abstract: SNS modulates colonic motility in patients with faecal urge incontinence. These data suggest that SNS may improve continence and urgency through alteration of colonic motility, particularly by increasing retrograde PSs in the left colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 45 publications
(62 reference statements)
7
99
1
Order By: Relevance
“…Another study of eleven patients demonstrated an increase in retrograde colonic propagating sequences with SES. This suggests that the effect of SES may be primarily on colonic motility rather than directly affecting external anal sphincter and puborectalis function [16,17]. Further studies investigating upper GI symptoms following single-device SES may be undertaken to further support this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…Another study of eleven patients demonstrated an increase in retrograde colonic propagating sequences with SES. This suggests that the effect of SES may be primarily on colonic motility rather than directly affecting external anal sphincter and puborectalis function [16,17]. Further studies investigating upper GI symptoms following single-device SES may be undertaken to further support this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…Proposed mechanisms of action include that SNS acts through a somatovisceral reflex pathway to reduce colonic activity, a direct effect on the anal sphincter complex to increase sphincter tone, reduce spontaneous sphincter relaxation, and change rectal sensitivity or compliance through afferent nerve modulation. [70-73] However, improvements in FI symptoms without changing sphincter pressures have also been reported. [70,74,75] Although data are limited, SNS has been shown effective in patients even with disrupted anal sphincters, including previously failed sphincteroplasty.…”
Section: Neuromodulationmentioning
confidence: 99%
“…[70-73] However, improvements in FI symptoms without changing sphincter pressures have also been reported. [70,74,75] Although data are limited, SNS has been shown effective in patients even with disrupted anal sphincters, including previously failed sphincteroplasty. The extent of sphincter gap differs in existing data; up to 180° sphincter separation has been studied.…”
Section: Neuromodulationmentioning
confidence: 99%
“…This study was uncontrolled. The mechanisms by which SNS improves fecal incontinence are unknown because effects on anorectal functions are relatively minor [66]. SNS but not sham stimulation increased the frequency of retrograde propagated sequences throughout the colon.…”
Section: Fecal Incontinencementioning
confidence: 99%
“…SNS but not sham stimulation increased the frequency of retrograde propagated sequences throughout the colon. Similar to anti-diarrheal agents, these effects may delay colonic transit [66]. …”
Section: Fecal Incontinencementioning
confidence: 99%